Are atypical antipsychotic medications better than the conventional ones? - Pedro Miguel Milián Vázquez; Lidia Vázquez Montero; Aldo Rodríguez Rodríguez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2005)
-